ANALISIS PERKEMBANGAN KINERJA KEUANGAN PADA PT. PUPUK SRIWIJAYA (Persero) PEMASARAN PUSRI DAERAH (PPD) BENGKULU - Sumantri, Bambang; Cahyadinata, Indra; Apriansyah, Yulian (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2007)
PT. Pupuk Sriwijya Pemasaran Pusri Daerah (PPD) Bengkulu is one suboffice of PT. Pusri Palembang. It has contribution to local government of Bengkulu in the term of channeling and distribution fertilizer to farmer and plantation companies. As the biggest fertilizer marketing company PT. Pupuk Sriwijaya PPD Bengkulu uses operating funding. Each company has objective to maximize profit and minimize cost. The financial ratio minimize cost depicts the financial performace in exploiting its assets, in other words, shows the financial of company. Main aspect in the assessment of financial performance is represented by good balance attainment between debt and assets. The results show that the financial performace of PT. Pupuk Sriwijaya PPD Bengkulu for 10 year (1997-2006) period in term of liquidity ratio is likuid, , in term of solvability ratio, the ratio above standard or it is solvable, looking at activity ratio, the company experience to continunes improvement every year, Then rentability ratio show the trend improvement every year and it has the high mean improvement. Base on these findings financial performace of PT. Pupuk Sriwijaya PPD Bengkulu shows a healthiness.